Mengapa Aku Dijauhkan? Jeritan Hati Orang dengan HIV Aids (ODHA): Upaya Tafsir Sosioretorik terhadap Markus 5: 25-34 - Ambarita, Sandora; Nababan, Celine; Sinambela, Lovina; Sihotang, Eleven (Sekolah Tinggi Diakones HKBP, 2025)
This article aims to examine the social experience of people living with HIV and AIDS (ODHA) through a socio-rhetoric interpretation of Mark 5:25-34. Using a socio-rhetoric approach, this article interprets the biblical text that tells the story of a woman who suffered bleeding for twelve years and was shunned by the community as a relevance of the experience of ODHA who are often marginalized and stigmatized. Findings show that the story reflects the social suffering experienced by ODHA and how Jesus modeled inclusive love and unconditional acceptance of marginalized individuals. This study proposes that ODHA can draw inspiration from this text to build an enthusiastic attitude in the healing process. The expected source of healing is the collaboration between the community and ODHA. The findings provide ethical insights in responding to the stigma against ODHA in Christian society.